Observer agreement for diagnosis of colorectal lesions with analysis of the vascular pattern by image-enhanced endoscopy - dos Santos, Carlos Eduardo Oliveira; Perez, Horácio Joaquin; Mönkemüller, Klaus; Malaman, Daniele; Lopes, César Vivian; Pereira-Lima, Júlio Carlos (Endoscopy International Open, 2015)
Background/Aims: Image-enhanced endoscopy (IEE) can differentiate neoplastic from non-neoplastic colorectal lesions through indirect analysis of pit patterns and microvascular architecture. We evaluated the accuracy of Flexible Spectral Imaging Color Enhancement (FICE) in differentiating neoplastic from non-neoplastic lesions and observer agreement in the analysis of capillary pattern of colorectal lesions.Methods: A prospective double-blind trial was conducted in two referral endoscopy centers. Vascular pattern was analyzed by IEE with magnification. Lesions were divided into two groups and examined separately by two experts. Examiners, blinded to each other’s interpretations, switched groups and the lesions were reviewed. After 60 days, lesions were reevaluated. Results: In total, 76 patients were referred to colonoscopy for colon cancer screening. Of 100 colorectal lesions, 88 were neoplastic (73 tubular adenomas, 10 tubulovillous adenomas, 1 villous adenoma, 2 serrated adenomas, 2 adenocarcinomas) and 12 were non-neoplastic (hyperplastic polyps). Mean diameter of the lesions was 6.7 mm. Examiners 1 and 2 had 95 % accuracy. The interobserver kappa coefficient was 0.80 and the intraobserver kappa coefficient was 0.88 for examiner 1 and 0.73 for examiner 2. Conclusion: IEE with magnification is effective for real-time predictive histological diagnosis of colorectal lesions, with inter- and intraobserver agreement ranging from good to excellent.